Psychosocial effects of cleft lip lip and palate patients aged 12 years and above in Malaysia - Chi Adam, Khairul Bariah; Ismail, Siti Mazlipah; Muhamad Halil, Mohd Haikal; Harun, Nor Adilah (2018)
Facial appearance is important in forming first impressions, and acts as a cue for social stereotyping (Tobiasen et al., 1987). There are evidence suggests that physical disfigurement is associated with greater internalizing behaviour (Richman and Millard, 1997). Cleft lip and palate deformities, for example, are considered as a stigma therefore many researches have been conducted to see the effects on patients’ psychology and psychosocial well-being. Owing to these deformities, cleft patients were perceived to have lower self-esteem, difficulty in the learning process, and tendency to be more depressed. They were also reported to have problems in their relationships with family and friends including being rated as less social and difficult to make new friends because of their deformity (Richman and Harper, 1980; Heller et al., 1981). Therefore, this prompted us to identify the effects of cleft on psychosocial development of a cleft child as well as the perceived psychosocial effects after receiving treatment in cleft lip and palate among individuals aged 12 years old and above in Malaysia. Questionnaire guided interview was done on 47 parents of cleft lip and palate patients from few centers in Malaysia to obtain demographic data and treatment history. The effects of cleft on the patients as well as perceived effects of treatment on their psychosocial behavior were rated in Likert scale. The results were found that cleft lip and palate deformity has the highest negative impacts on the patients’ behavior. This is followed by confidence, academic achievement as well as social ability. Parents perceived that their child’s social capability will be positively affected (moderate to most) after further treatment (74.5%) as compared to the effect on their child’s current condition (44.7%). Only 12.8% of the parents felt that further treatment will give no effect on their child’s capability to socialize. As a conclusion, cleft lip and palate deformity have negative impacts on psychosocial behaviour of the cleft patients and treatment to correct these deformities were perceived to improve these impacts on the cleft patients.